Methylprednisolone Induces Neuro-Protective Effects via the Inhibition of A1 Astrocyte Activation in Traumatic Spinal Cord Injury Mouse Models - Zou, Hong-jun; Guo, Shi-Wu; Zhu, Lin; Xu, Xu; Liu, Jin-bo (Frontiers in Neuroscience, 2021)
Traumatic spinal cord injury (TSCI) leads to pathological changes such as inflammation, edema, and neuronal apoptosis. Methylprednisolone (MP) is a glucocorticoid that has a variety of beneficial effects, including decreasing inflammation and ischemic reaction, as well as inhibiting lipid peroxidation. However, the efficacy and mechanism of MP in TSCI therapy is yet to be deciphered. In the present study, MP significantly attenuated the apoptotic effects of H2O2 in neuronal cells. Western blot analysis demonstrated that the levels of apoptotic related proteins, Bax and cleaved caspase-3, were reduced while levels of anti-apoptotic Bcl-2 were increased. In vivo TUNEL assays further demonstrated that MP effectively protected neuronal cells from apoptosis after TSCI, and was consistent with in vitro studies. Furthermore, we demonstrated that MP could decrease expression levels of IBA1, Il-1α, TNFα, and C3 and suppress A1 neurotoxic reactive astrocyte activation in TSCI mouse models. Neurological function was evaluated using the Basso Mouse Scale (BMS) and Footprint Test. Results demonstrated that the neurological function of MP-treated injured mice was significantly increased. In conclusion, our study demonstrated that MP could attenuate astrocyte cell death, decrease microglia activation, suppress A1 astrocytes activation, and promote functional recovery after acute TSCI in mouse models.